Optimizing Pancasila Education Through Modern Teaching Materials: A Need Analysis for Effective Learning - Tarisa Jayanti; Wuri Wuryandani; Setiawan Edi Wibowo; Jaka Pasa Tribrata (STAI Hubbulwathan Duri, 2025)
Pancasila Education plays a vital role in shaping student character in line with national values. However, its implementation in schools often remains suboptimal and does not reflect the evolving characteristics and needs of today’s learners. This study investigates the necessity for innovative, technology-integrated teaching materials to enhance the effectiveness of Pancasila Education. This qualitative research employed a case study approach. Data were collected through observations, interviews, questionnaires, and document analysis, involving teachers and students as key participants. The findings reveal a strong need among teachers for innovative and student-centred teaching materials, particularly those that leverage digital technologies to make learning more relevant and engaging. Although many schools are equipped with adequate technological infrastructure, teachers often face challenges in designing and integrating technology-based instructional tools into Pancasila Education. These challenges stem primarily from a lack of training and limited access to appropriate digital teaching resources. To optimize Pancasila Education, it is essential to develop teaching materials aligned with both technological advancements and students' learning characteristics. Teacher capacity-building programs focusing on digital pedagogy and instructional design are recommended. These efforts will not only improve the learning experience but also ensure that Pancasila values are effectively internalized by students in a way that resonates with the digital era.